2019
DOI: 10.1002/nsg.12030
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrical conductivity and water content of peat and gyttja: implications for electrical surveys of drained peatlands

Abstract: The application of electrical resistivity tomography to peatlands supports conventional coring by providing data on the current condition of peatlands, including data on stratigraphy, peat properties and thickness of organic deposits. Data on the current condition of drained peatlands are particularly required to improve estimates of carbon storage as well as losses and emissions from agriculturally used peatlands. However, most of the studies focusing on electrical resistivity tomography surveys have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Gyttjas exhibit heightened organic matter and water content relative to the underlying mineral parent material, which results in contrasts in the electrical properties [73]. Additionally, gyttja types vary greatly in their mineral composition and organic matter content [17,74], which can lead to site-specific contrasts at the interfaces between different gyttja layers [73,[75][76][77]. Therefore, we employ geophysical techniques that are sensitive to electrical conductivity and dielectric permittivity contrasts, namely Electromagnetic Induction (EMI) and Ground-Penetrating Radar (GPR) (cf.…”
Section: Prospection Conceptmentioning
confidence: 99%
“…Gyttjas exhibit heightened organic matter and water content relative to the underlying mineral parent material, which results in contrasts in the electrical properties [73]. Additionally, gyttja types vary greatly in their mineral composition and organic matter content [17,74], which can lead to site-specific contrasts at the interfaces between different gyttja layers [73,[75][76][77]. Therefore, we employ geophysical techniques that are sensitive to electrical conductivity and dielectric permittivity contrasts, namely Electromagnetic Induction (EMI) and Ground-Penetrating Radar (GPR) (cf.…”
Section: Prospection Conceptmentioning
confidence: 99%
“…Groundwater level also affects the physical properties of the peat. (Walter, Lück, Heller, Bauriegel, & Zeitz, 2019) have shown that different levels of water saturation strongly influence bulk electrical conductivity (reciprocal of resistivity). In dry season groundwater level fall far below the surface, thereby decreasing moisture contents of the surface peat and creating vast amounts of dry fuel that are a fire hazard (Wösten, Clymans, Page, Rieley, & Limin, 2008).…”
Section: A Ert Section Prg-2mentioning
confidence: 99%
“…Using three different mires located over the Stolowe Mountains (central Sudetes) we tested the application of integrating digital elevation models, remote sensing data and shallow geophysical prospecting methods (electrical resistivity tomography and ground penetrating radar) to delineate the extent of mires, their thickness, internal structure, and basement morphology. Our approach was guided by the effectiveness of those geophysical methods proven in investigations on other wetlands [10][11][12][13][14][15][16], the proven applicability of remote sensing in the analysis of diversity of vegetation and monitoring of changes in biodiversity [17,18], as well as the analytical potential of LiDAR-based DTM shown for the Stolowe Mountains National Park in Poland [19].…”
Section: Introductionmentioning
confidence: 99%